Modelling inductively coupled plasmas: a sensitivity study on plasma chemistry and surface chemistry - Nold, Michael; Kleditzsch, Stefan; Riedel, Uwe (Surface and coatings technology, 2001)
The knowledge of electron heavy-particle interactions plays a crucial role in the modelling of plasma etch processes. Usually these interactions are computed from collision cross-sections, which are obtained from experiments or ab-initio calculations. However, either method has its uncertainties. This paper investigates the influence of these uncertainties on gas phase composition and state of the surface. The collision cross-sections of all inelastic interactions in a chlorine/argon-plasma are systematically varied in sensitivity studies. A spatially averaged model is used to calculate plasma and surface composition. First the electron distribution function (EEDF) is solved. Followed by the solution of the species and energy conservation equations. The results identify important electron heavy-particle processes in the etching process. Though results are presented for the Cl2/Ar-system only, the method is also applicable to other chemical systems and the volume averaged approach is fast enough to allow for extensive parametric studies.
Gesehen am 04.10.2017